Gabriel Lippmann (1845–1921) & Frederick Ives (1856–1937): The French Physicist Versus The American Inventor in the Pursuit of Colour and 3-Dimensionality (International Journal on Stereo & Immersive Media, 2021)
I explore the reception to photographic invention at the end of the nineteenth century and how photographic practice was embraced by the Academy with Lippmann’s Nobel Prize-winning process. Whereas Lippmann published a theory in the public domain, a requirement for the Nobel Prize, Ives was dependent on commercial sales. However, Ives was a critic of Lippmann’s process which competed with his own efforts for display and publicity. Here, I review the division of theory with mechanical invention that existed between Lippmann’s and Ives’ 3-Dimensional concepts. And I discuss the assessment by Herbert Ives (1882–1953), the son of Frederick Ives, of both these inventions.